PERAN SANGGAR SENI PARANTA’TAU DALAM MEMBENTUK KARAKTER SISWA MELALUI SENI TEATER DI SMA - Indah, Laysius; Nurlela, Nurlela; Junaeda, St. (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study examines in depth the role of the Paranta’Tau Art Studio at SMA Negeri 13 Makassar in influencing students during their participation in theater arts training. The researcher uses a descriptive type of research employing qualitative data. Data collection was obtained through field observation, interviews, documents, and documented photographs. The data obtained were then analyzed using Malinowski's Functionalism perspective. The results of the study indicate that the Art Studio not only functions as a place for talent development but also as a social institution that maintains balance and order in the implementation of activities within the school environment. The balance referred to is between the achievement of academic learning outcomes in the classroom and the non-academic activities of the Art Studio, including the formation of students' character. The implications of the Paranta’Tau Art Studio suggest that this activity strengthens social bonds, group solidarity, and a sense of belonging among the studio members. Theater arts serve as a space for social integration that assists students in developing their self-identity within the school community. ABSTRAK Penelitian ini membahas secara mendalam bagaimana peran dari Sanggar Seni Paranta’Tau SMA Negeri 13 Makassar dalam memberikan pengaruh bagi siswa selama mengikuti pelatihan seni teater. Peneliti mrnggunaksn jenis penelitian deskriptif dengan menggunakan data kualitatif. Pengumpulan data diperoleh dengan melakukan observasi lapangan, wawancara, dokumen, dan dokumentasi berupa foto. Data yang telah diperoleh kemudian dianalisis menggunakan persfektif Fungsionalisme dari Malinowski. Hasil penelitian yang didapatkan, menunjukkan bahwa Sanggar Seni tidak hanya berfungsi sebagai tempat pengembangan bakat, tetapi juga sebagai lembaga sosial yang menjaga keseimbangan dan keteraturan pelaksanaan kegiatan di lingkungan sekolah. Keseimbangan yang dimaksudkan adalah antara capaian hasil pembelajaran dikelas yang sifatnya akademik dengan kegiatan Sanggar Seni yang non-akademik, termasuk pebentukan karakter siswa. Implikasi dari Sanggar Seni Paranta’Tau menunjukkan bahwa kegiatan ini memperkuat hubungan sosial, solidaritas kelompok, serta rasa memiliki di antara anggota sanggar. Seni teater menjadi ruang integrasi sosial yang membantu siswa membangun identitas diri dalam komunitas sekolah.